Analysis of dairy cattle feed as source of heat resistant bacterial spores in milk and evaluation of contamination consequences for milk quality : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Microbiology at Massey University, Palmerston North, New Zealand - Flossdorf, David (Massey University, 2021)
Spore-forming bacteria are resistant to heat treatments designed to control the growth of other bacteria and can impact the quality of milk. Bacterial spores in milk are hypothesised to originate from cattle feed, among other sources. In recent decades, supplementary feed usage and variability of used feed types has increased in New Zealand. To ensure low numbers of bacterial spores in dairy products, the number of spores in common New Zealand dairy cattle feed and milk were observed at psychotropic, mesophilic and thermophilic temperatures under aerobic and anaerobic conditions and the bacterial spore species found were identified. Differences were detected in the number of bacterial spores and variety of species present, between sample types. Tuber feed and palm kernel expeller (PKE) contained the greatest quantity of spores as well as the greatest diversity of bacterial spore species, while milk contained the lowest quantity and diversity. This supports a hypothesis that some cattle feeds are more likely to be a source of milk contamination than others. Almost all (96 %) of bacterial spore species found in milk were also found in cattle feed, indicating that spores may transfer from feed to milk. To provide more definitive evidence of the transfer of bacterial spores from cattle feed to milk, the genomes of 109 bacterial isolates from milk and feed were sequenced and compared. Clusters of similar genomes were found between milk and feed isolates, however within the set criteria of the study, no match was found. A greater genomic diversity was observed in cattle feed compared to milk. A lower genomic diversity was observed among Bacillus licheniformis and B. pumilus isolates compared to isolates from B. cereus, B. mycoides or B. thermoamylovorans. Not all spore-forming bacteria isolates cause issues in milk production therefore the potential of bacterial spores isolated from raw milk, to damage milk was determined. A set of 20 bacterial spore isolates were screened for their ability to grow in milk, form biofilms, produce milk damaging enzymes and resist heat treatment. All isolates grew in milk, almost all had some ability to produce biofilm on stainless steel and produce milk degrading enzymes. Differences in biofilm production and heat resistance of spores were found between the isolates. Out of all isolates, two B. licheniformis isolates were found to possess the greatest potential to damage milk and whole genome data was used to investigate the genes responsible for differences in the milk damaging abilities. A set of gene alleles was identified which might affect the potential of an isolate to influence milk quality. Highlights: • Determining the bacterial spore diversity in current New Zealand cattle feed and milk • The potential of comparative genomics to trace bacterial spores between cattle feed and milk • Characterisation of the milk damaging potential of common bacterial spore isolates from milk • Identification of spore-forming bacteria genes responsible for a high milk damaging potential in isolates. Limitations: • Only the most popular feeds were analysed. • Culture dependant methods were used for most of the work. • Tracking bacterial spores from feed to milk involved multiple species across multiple farms rather than a more intensive study of a single spore species on a single farm. • Milk damaging potential was assessed for only of subset of the most common isolates of bacterial spores found in milk.
Keywords: Dairy cattle; Feeding and feeds; New Zealand; Bacterial spores; Milk contamination; Milk; Quality; 310701 Bacteriology